Pengaruh Analisis Jabatan terhadap Kinerja Karyawan dalam Mencapai Tujuan Organisasi - Samsudin, Acep; Prabowo, Budi; Alichia, Wanda Noer; Al-Madani, Bintaniya Zakka; Renardi, Asyam Rafi (Ikatan Da'i Indonesia, 2024)
This research aims to understand the influence of job analysis on employee performance. With this job analysis, it can make it easier for organizations to direct human resources to carry out their duties, as well as influence employee performance so that they carry out their duties well, so that organizational goals will be achieved. The method used in this research is qualitative with a literature study approach. Meanwhile, collecting data and study materials through various journals relevant to the research. Then a conclusion can be drawn that job analysis greatly influences employee performance which is the main factor in achieving organizational goals.